PENGARUH MODAL INTELEKTUAL DAN KINERJA KEUANGAN TERHADAP NILAI PASAR - Nurlaela Marjuwita; Ibnu Hajar; Yusuf Montundu (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2017)
This study aims to determine and analyze the influence of intellectual capital and financial performance on market value (studies of banks listed on the Indonesia Stock Exchange).The design of this study is associative research (cause and effect). The object of this research is the market value of banks listed on the Indonesia Stock Exchange. The research sample was determined by purposive sampling as many as 10 banks, where each bank was taken financial report data for the last three years (2013-2015). The type of data in this study consists of quantitative data and qualitative data. While all data sources are secondary data. Data collection using documentation studies. The analysis used is descriptive statistical analysis and multiple linear regression analysis.The results of the study concluded that: 1) Intellectual capital and financial performance together have a positive but not significant effect on market value in banks listed on the Indonesia Stock Exchange. That is, an increase in intellectual capital and financial performance cannot increase market value in banks listed on the Indonesia Stock Exchange which are implemented at price earnings ratio (PER) and price to book value (PBV). 2) Intellectual capital has a positive but not significant effect on the market value of banks listed on the Indonesia Stock Exchange. This means that the increase in intellectual capital at the value added capital employed (VACA), value added human capital (VAHU) and structural capital value added (STVA) cannot significantly increase the market value of banks listed on the Indonesia Stock Exchange. 3) Financial performance has a positive but not significant effect on market value in banks listed on the Indonesia Stock Exchange. That is, an increase in financial performance proxied from return on assets (ROA), return on equity (ROE) and net profit margin (NPM) cannot significantly increase the market value of banks listed on the Indonesia Stock Exchange.Keywords:Intellectual Capital, Financial Performance, Market Value